The Tibbitt to Contwoyto winter road in the NWT: identification of available data and research needs - Barrette, Paul Dominique (National Research Council of Canada. Canadian Hydraulics Centre, 2011)
Information on the Tibbitt to Contwoyto Winter Road north of Yellowknife was acquired by the author during a three-day field trip in March 2008. The construction and maintenance of this road, most of which is constructed over frozen lakes, is managed by the Joint Venture Management Committee (JVMC). It is a major access road to supply several mine sites. Build-up initiation occurs in December. When the ice thickness is deemed adequate, crews get on the ice with light vehicles. EBA engineers are in charge of design ice thickness, so as to ensure they can meet minimum ice thickness criteria. Flooding with pumps is used to improve ice surface quality and also increases the thickness of the ice cover. The ice road is a public-private road. Permitted speeds range from 10 to 35 km/h, but can go up to 60 km/h on expressways. Outstanding issues raised by JVMC include means of extending the season, how to mitigate the effects of blow-outs, and what is the role of load-induced crack accumulation. Ce rapport résume les observations recueillies par l’auteur au cours d’un séjour de trois jours en mars 2008 sur la route d’hiver Tibbitt-Contwoyto, au nord de Yellowknife. La construction et l’entretien de cette route, en grande partie sur des lacs gelés, est l’affaire de la « Joint Venture Management Committee » (JVMC). Il s’agit d’une voie d’accès importante pour le soutien logistique de plusieurs sites miniers. Sa construction débute en décembre. Lorsqu’on juge l’épaisseur de la glace suffisante, le personnel a recours à des véhicules légers pour y circuler. À l’aide de certains critères, les ingénieurs de EBA établissent l’épaisseur minimale requise pour un accès sécuritaire. En pompant l’eau sur la glace, on améliore la qualité de la surface tout en contribuant à en augmenter l’épaisseur. Cette route est la fois publique et privée. La vitesse autorisée varie de 10 à 35 km/h, mais peut aller jusqu’à 60 km/h dans les voies rapides. La JVMC a soulevé certaines questions qu’il reste encore à éclaircir. Par exemple, comment ...